Análise sensorial e composição centesimal de carne de jacaré-do-papo-amarelo (Caiman latirostris) em conserva - Azevedo, Isabela Ciarlini de (2007)
This work focused on the evaluation of three broad-snouted caiman (Caiman latirostris) canned meat formulas: one in edible oil, another in salt with onions, and the third one in seasoned salt. The animals were acquired from the Criadouro Comercial Arurá (Barra Mansa/RJ). Eleven cuts (six pairs of members, one tail, two ribs and two loins) were separated after slaughter to produce the canned meat. Gas chromatographic analysis of the fatty acids in the non-processed meat was conducted before industrial processing. The canning process took place at the Fábrica de Conservas Rubi (São Gonçalo/Rio de Janeiro), adding up to about 60 cans of 180 g each. A commercial sterility test for low acidity food was conducted for the canned meat samples. Subsequently, the three formulations were tested for their sodium chloride content and sensory acceptance (9-point hedonic scale) with respect to their appearance and global impression. The pH and percent composition (moisture, fixed mineral residue, proteins and lipids contents) of both the non-processed meat and the canned meat samples were determined so that the product s nutritional value could be evaluated and the mandatory nutritional label could be prepared in detail. The saturated, monounsaturated and polyunsaturated fatty acids values were, respectively, 28,5; 42,5 and 29,0% of the total fatty acids in the non-processed meat. The canned meat samples were released after verifying that there were no leaking or blown cans in the sterility test. The sodium chloride content was in the range of 0,52 to 1,25%, where the highest value was found for the samples in salt. The three samples were significantly different in respect to appearance. The results showed the following order, from the least to the most acceptable sample: salt with onions, seasoned salt and edible oil. As for the global impression, the formulation in edible oil was also the most acceptable. The non-processed broad-snouted caiman meat had an average pH of 5,91, 79,05% moisture content and 0,77% of fixed mineral residue, a protein concentration of 19,81% and a total lipid content of 3,11%. The canned meat samples had a lower pH, similar moisture percentage, higher fixed mineral residue content, and a lower protein concentration due to the addition of other ingredients. The sample in edible oil showed a higher concentration of lipids (12,77%). One can conclude from these results that it is possible to commercialize canned broad-snouted caiman meat, which allows a better use of the meat after the slaughter. There were also an increase in the value added and a good sensory acceptance of the product